2019
DOI: 10.1007/jhep04(2019)045
|View full text |Cite
|
Sign up to set email alerts
|

Gluing together modular flows with free fermions

Abstract: We revisit the calculation of multi-interval modular Hamiltonians for free fermions using a Euclidean path integral approach. We show how the multi-interval modular flow is obtained by gluing together the single interval modular flows. Using this relation, we obtain an exact expression for the multi-interval modular Hamiltonian and entanglement entropy in agreement with existing results. An essential ingredient in our derivation is the introduction of the modular action. This determines the non-local field the… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
13
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 14 publications
(13 citation statements)
references
References 15 publications
0
13
0
Order By: Relevance
“…The modular flow corresponding to this modular Hamiltonian and the entanglement entropy for several intervals have been computed in [22]. Recently, the modular Hamiltonian has also been computed using Euclidean path integral methods in [24]. In [23] it was shown that the modular flow satisfies the KMS condition.…”
Section: Modular Hamiltonianmentioning
confidence: 99%
See 1 more Smart Citation
“…The modular flow corresponding to this modular Hamiltonian and the entanglement entropy for several intervals have been computed in [22]. Recently, the modular Hamiltonian has also been computed using Euclidean path integral methods in [24]. In [23] it was shown that the modular flow satisfies the KMS condition.…”
Section: Modular Hamiltonianmentioning
confidence: 99%
“…In more generality, it is possible to identify a local part of the modular Hamiltonian which should have a large degree of universality [20,21], while not much is known about non local terms. An example of non local modular Hamiltonian which has been explicitly computed is for the vacuum state of the free massless fermion in d = 2 [22] (see also [23,24]). In this case H for several disjoint intervals has a local term proportional to the energy density and an additional non local part given by a quadratic expression in the fermion field.…”
Section: Introductionmentioning
confidence: 99%
“…9. It would be also interesting to apply the present formalism to the calculation of the entanglement entropy for multiple sections [44][45][46][47][48][49]. These possibilities will be pursued in future research.…”
Section: Discussionmentioning
confidence: 99%
“…For the case of the Ising model CFT, [35] showed how the entanglement entropy depends on these Cardy states and how they are mapped to entanglement boundary conditions of the microscopic model. In [36], the multi-interval modular Hamiltonian was obtained by incorporating the cutting and gluing operations that are manifest in the cobordism of figure (2). These examples give some hints for how to incorporate entanglement calculations in the framework of extended CFT.…”
Section: Discussionmentioning
confidence: 99%